A novel nomogram based on complement C3 to predict the overall survival of early-stage hepatocellular carcinoma patients with microvascular invasion-positive undergoing curative resection - Xia, Guoyi; Yu, Zeyan; Lu, Shaolong; Wang, Xiaobo; Zhao, Yuanquan; Chen, Jie (Frontiers in Oncology, 2025)
PurposeThis investigation aimed to create a new nomogram based on complement C3 to forecast 1-, 3-, and 5-year overall survival (OS) rates in patients with early-stage hepatocellular carcinoma (HCC) exhibiting microvascular invasion (MVI) post-curative surgery.MethodsThis study encompassed 1234 patients treated with resection at the Affiliated Cancer Hospital of Guangxi Medical University. The cohort for primary included 865 patients from December 2015 to December 2019, while the validation cohort comprised 369 patients. Follow-ups were conducted regularly until December 2024. Variables predicting survival were identified using Cox regression analyses, and based on these, a nomogram was constructed. This nomogram’s accuracy was assessed via time-dependent ROC curves, calibration curves and KM curve analyses.ResultsInvestigations identified complement C3, PT, the presence of cirrhosis, tumor capsule, and MVI-M2 as distinct predictors of survival in HCC patients. Based on these findings, a predictive nomogram was constructed and validated, aimed at estimating the 1-, 3-, and 5-year OS. The efficacy of the nomogram was validated through analyses with ROC curves, calibration curves, each demonstrating positive outcomes. Additionally, KM curve analysis effectively separated the patient populations into two prognostic risk categories within both the primary and validation cohorts.ConclusionIn conclusion, a new nomogram has been developed and corroborated through multivariate Cox regression analysis, aimed at estimating overall survival for patients in early stages of microvascular invasion following surgical resection. This tool has proven to be more effective in forecasting survival outcomes for such patients post-curative surgery.